Experimental transmission of Enteromyxum scophthalmi (Myxozoa), an enteric parasite of turbot Scophthalmus maximus - Redondo, Mª José; Palenzuela, Oswaldo; Riaza, Ana; Macías, M. A.; Álvarez-Pellitero, Mª del Pilar (BioOne, 2002)
Several experiments were designed to elucidate the modes of transmission of the myxozoan parasite Enteromyxum scophthalmi to turbot Scophthalmus maximus. Direct transmission of the infections was achieved by cohabitation of infected and test fish, through waterborne contamination from the effluent of a tank containing infected fish, and via the oral route using parasite-infected intestines. The transmission of the turbot enteromyxosis was successful in all the fish exposed to the parasite by the 3 routes; accumulated mortality reached 100% at the end of most experiments. The progress of the infections was monitored by study of the histopathology, Influence of the mode of exposure was observed, with the oral route the fastest to initiate the parasite infections. The temperature also affected the course of the infections, which were established earlier at higher water temperature. Direct fish-to-fish transmission of the disease explains the rapid spreading of the turbot enteromyxosis in farms. Funding for this study was provided by the EU and the Spanish Government through the research grant FEDER 1FD97-0679-C02-01. We are grateful to J. Monfort for the histological processing.